Study on CEO characteristics for management of public art performance centers - Joon-ho Kim; Seung-hye Jung (Journal of Open Innovation: Technology, Market, and Complexity, 2015)
The purpose of this study is to present the rationale and empirical evidence as to whether the characteristics of chief executive officer (CEO), such as entrepreneurship, social responsibility (perception), and social capital, at public art performance centers have effect on management outcomes, and to find if quality management activities have significant effects on business performance. The analysis was carried out with the structural equation model by using the survey data on 98 CEOs at public art performance centers. After the analysis, it was shown that the entrepreneurship, social responsibility (perception), and social capital have positive (+) effects on quality management activities, and quality management activities have positive (+) effects on business performances (market performance, financial performance). Therefore, as the local cultural center, the public art performance centers should take social responsibility and role, while being financially productive through effective operation. Furthermore, CEO of public art performance centers should have expertise in the fields of art and performances, productions, and advertising. For the management and enhancement, entrepreneurship and broad social network is also necessary.
Keywords: 650; Public art performance centers; CEO; Entrepreneurship; Social responsibility; Social capital; Quality management activities; Business performance